De-stigmatizing the "win–win:" making sustainable consumption sustainable. (August 2022) - Goldsmith, Kelly; Roux, Caroline; Tezer, Ali; Cannon, Christopher
Abstract: In this article, we review research on the discrepancy between consumers' high self-reported interest in sustainable products and these products' poor performance in the marketplace. We offer theoretically derived reasons for why framing sustainable products as "win-wins" (i.e., offering benefits to the self and to the greater good) might present a solution to this intention-behavior gap. Although prior research has typically found negative effects of win–win framing on sustainable consumption, we propose framing sustainable consumption as a win–win provides greater environmental, behavioral, and psychological benefits than framing it only in terms of benefits to the self or to the greater good. We discuss how these outcomes may operate due to differences in moral hypocrisy, licensing, and goal representation, and offer avenues for future research to test these moderators in an effort to improve the efficacy of win–win framing.